Ионизационный отжиг полупроводниковых кристаллов. Часть первая: Теоретические предпосылки - Garkavenko, A. S.; Mokritskii, V. A.; Banzak, O. V.; Zavadskii, V. A. (PE "Politekhperiodika", Book and Journal Publishers, 2014)
During irradiation of semiconductor crystals with powerful (high current) pulsed high-energy electron beams, a new type of annealing has been obtained. We could obtain new results and to find out physical nature of this phenomenon due to short and powerful bunches of electrons with high energy. Given its theoretical justification, the new annealing type has been called the "ionization annealing".